Policy design for democracy - Schneider, Anne Larason; Ingram, Helen M. 1937- (Univ. Press of Kansas, 1997)
How can democracy be improved in an age when people are profoundly disenchanted with government? Part of the answer lies in the design of public policy that unmistakably works to advance citizenship by listening to, educating, and involving ordinary people. Schneider and Ingram evaluate the current approaches to policy theory and recommend a series of reforms that will improve policy designs and help restore citizen confidence in government. Policy Design for Democracy is one of the first books to examine systematically the broader implications of the substantive aspects of public policy.
Keywords: Beleidswetenschap; Democracia; Democracia - EE.UU; Democratie; Démocratie; Démocratie - États-Unis; Politique publique - États-Unis; Sciences de la politique; Demokratie; Democracy; Democracy -- United States; Policy sciences; Political planning -- United States; Politische Wissenschaft; Politische Theorie; Politische Planung; EE.UU - Política y gobierno; USA